The Role of Work Environment, Motivation, and Discipline in Improving Teacher Performance - Amaliah, Rizki; Rina, Rina; Nuryadin, A (International Journal of Business, Law, and Education, 2025)
This study aims to analyse the effect of work environment, work motivation, and work discipline on teacher performance in Tanralili Sub-district, Maros, both partially and simultaneously. Data were collected through distributing questionnaires to 191 respondents, and data were analysed using multiple linear regression method. The results showed that the work environment has a significant positive effect on teacher performance, especially through aspects of work facilities and communication that create a conducive work atmosphere. However, work motivation, measured through physical needs such as rewards in the form of salary, shows a negative influence on teacher performance, indicating that financial motivation alone is not enough to optimise performance. Work discipline, measured through attendance and vigilance indicators, also has a negative influence on performance, although it remains an important factor in supporting performance improvement. Simultaneously, these three variables contribute 9.5% to teacher performance, while the remaining 90.5% is influenced by other factors such as competence, leadership style, or social environment. The F test results show a significant joint effect of these variables on teacher performance. The implications of these findings underscore the importance of performance improvement strategies through improving the work environment, providing more thorough motivation, and improving discipline holistically